Dasatinib first-line: Multicentric Italian experience outside clinical trials. (January 2016) - Breccia, Massimo; Stagno, Fabio; Luciano, Luigiana; Abruzzese, Elisabetta; Annunziata, Mario; D'Adda, Mariella; Maggi, Alessandro; Sgherza, Nicola; Russo-Rossi, Antonella; Pregno, Patrizia; Castagnetti, Fausto; Iurlo, Alessandra; et al.
Highlights: Dasatinib, a second generation TKI, can be prescribed as frontline treatment. Lower median age and higher incidence of high Sokal risk were observed in a multicentre population treated outside clinical trials. Increased rate of molecular responses similar to that reported in sponsored trials. The results confirmed the low rate of progression. Abstract: Dasatinib was approved for the treatment of chronic phase (CP) chronic myeloid leukemia (CML) patients in first line therapy based on the demonstration of efficacy and safety reported in patients enrolled in clinical trials. We describe a multicentric Italian "real-life" experience of dasatinib used as frontline treatment outside clinical trials. One hundred and nine patients (median age 54 years) were treated from January 2012 to December 2013. Increased incidence of high risk patients were detected according to stratification (26% according to Sokal score, 19% according to Euro score and 16% according to EUTOS) when compared to company sponsored studies. Median time from diagnosis to start of dasatinib was 18 days. Ten patients received unscheduled starting dose (6 patients 50 mg and 4 patients 80 mg QD), whereas 99 patients started with 100 mg QD. At 3 months, 92% of patients achieved a BCR-ABL ratio less than 10%. At 6 months, the rate of CCyR was 91% and the rate of MR3 was 40%, with 8% of the patients reaching MR4.5. Ninety-three patients were evaluable at 12 months: the rate of MR3 was 62%, with MR4.5 being achieved by 19% of the patients. At a median follow-up of 12 months, 27 patients (24.7%) were receiving the drug at reduced dose. Two patients (1.8%) experienced a lymphoid blast crisis and the overall incidence of resistance was 8%. As regards safety, the major side effects recorded were thrombocytopenia, neutropenia and pleural effusions, which occurred in 22%, 10% and 8% of patients, respectively. Present results, achieved in a large cohort of patients treated outside clinical trials, further confirm the efficacy and safety of dasatinib as firstline treatment in CML.